LINGUISTIC LANDSCAPE AND THE MONOLITHIC NATURE OF THE EU - Bohdan Yuskıv; Nataliia Karpchuk (Ankara Avrupa Çalışmaları Dergisi)
Multilingualism is one of the EU's integrity cornerstones. However, language policy is a matter for each Member State to seek to meet the EU's multilingualismrequirements and to ensure the integration of its own society. The purpose of the article is to substantiate that effective communications based on multilingualismdevelopment contribute to strengthening the monolithic nature of European states unification within the EU structure. The system of generalized indices, cluster andfactor analyses made it possible to prove that the higher the level of the linguistic landscape is, i.e., the higher the level of multilingualism, the higher the level ofmonolithic nature of the unification. In this article the factors that contribute to the development of the EU Member States linguistic landscape have been identified.